Education faculty as knowledge brokers: Competing for access to New York State print media and policy influence - Anderson, Gary; Gray-Nicolas, Nakia M.; Payton, Madison (Education Policy Analysis Archives, 2021)
In an environment in which new policy entrepreneurs and networks are influencing policy and public opinion, many university faculty are increasingly seeking ways to mobilize knowledge beyond academic conferences and journals. Using New York state as a case, we searched Access World News to compare the level of media access of academics with other knowledge brokering organizations (KBOs; e.g. think tanks, teachers’ unions, advocacy organizations, etc.). Our data shows relatively low levels of access for academics and provides profiles of those academics with high levels of access and what we might learn from them. We provide a discussion of the strategies of those academics who are successful at accessing the media and how disinvestment by the state from higher education and current incentive systems make it more difficult for academics to engage in knowledge mobilization beyond universities.